PERSEPSI MASYARAKAT TENTANG PERANAN POLRI DALAM MENANGGULANGI PENYALAHGUNAAN NARKOBA DI KALANGAN REMAJA DI KECAMATAN TUALANG KABUPATEN SIAK - Imam Fatoni; Hambali Hambali; Gimin Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to knowing people’s perceptions about the role of The Indonesian Republican Police Force in overcoming drug abuse among teenagers in Tualang Sub-District Siak District. Respondent in this research were 100 person by using Proportional Area Sampling Technique. Data collection techniques that are carried out namely through observation, questionnaire, interview, library and documentation. The research method used is mixed research namely quantitative and qualitative descriptive analysts. This method is done with processing data whose data results presented through percentage calculation from the questionnaire and the respondent’s description from the interview. Based on the rseults of the research conducted regarding people’s perceptions about the role of the national police in overcoming drug abuse among teenagers in Tualang Sub-District Siak District, it can be conclued that overall data about the role of the national police in overcoming drug abuse in range 0% - 25% then the range is included to the range “Not Good” with the acquestion of a percentage of 45%. Based on the results of the study and data analysis, then the researcher providers recommendations namely to the local police in Tualang Sub-District Siak District in this case it is Tualang Police to be able to improve performance and effort in combating and overcoming drug abuse in Tualang Sub-District Siak District.Key Words: The Role Of The National Police, Overcome, Drugs